Dioxidovanadium(V) complexes of a tridentate ONO Schiff base ligand: Structural characterization, quantum chemical calculations and in-vitro antidiabetic activity. (1st April 2020) - Patel, Neetu; Prajapati, A.K.; Jadeja, R.N.; Patel, R.N.; Patel, S.K.; Tripathi, I.P.; Dwivedi, N.; Gupta, V.K.; Butcher, Raymond.J.
Graphical abstract: Two VO(V) complexes have been synthesized and structurally characterized. Their structural features have been assessed and in vitro anti diabetic activity is also reported. Abstract: Two new dioxidovanadium(V) complexes [V(O)2 (L)]Him 1 and [V(O)2 (L)]H2Meim 2, incorporating tridentate ligand Nicotinic acid (2-hydroxy-3-methoxy-benzylidene)-hydrazide (H2 L) and imidazoles (Him = imidazole and H2Meim = methylimidazole) was substantiated. The crystal structures of both complexes were solved by single-crystal X-ray analysis. In both complexes, the V(V) center is coordinated by ONO donar set of L 2 - ligand and two oxido groups in a distorted square pyramidal geometry. UV–visible spectra, infrared spectra and electrochemical properties of both complexes were also reported. Room temperature magnetic susceptibility was performed to disclose the diamagnetic nature of complexes 1 and 2 . The quantum chemical calculations authenticated the molecular structures and reactivity of the complexes. Antidiabetic activities of the complexes have also been investigated. An antidiabetic feature like α-amylase and α-glucosidase inhibition studies made them promising agents as inhibitors of insulin enzyme.